No Thesis, No Future! Exploring the associations between research inaccessibility and suicidal ideation - Md. Abu Huraira; Md. Maruf Khan; Momotaj Begum; Pronab Das; Md. Omar Faruk; Sadikur Rahman; Sabrina Aktar; Md Zahidul Hasan; Moneerah Mohammad ALmerab; Remya Lathabhavan; Firoj Al-Mamun; Mohammed A. Mamun (PLoS ONE, 2026)
Background Suicidal ideation is a pressing mental health concern among university students, especially in low- and middle-income countries like Bangladesh, where academic pressure, research-related stress, and limited support systems heighten the risk. While mental health conditions such as depression and anxiety are known predictors, the role of academic research involvement—particularly thesis engagement, supervision, and institutional support—remains underexplored and is examined in this study. Methods A cross-sectional study was conducted among 508 university students and recent graduates in Bangladesh using a structured questionnaire. Data were analyzed using descriptive statistics, Chi-square tests, and binary logistic regression to examine associations between suicidal ideation and psychological, academic, and institutional factors, while QGIS was used to conduct geospatial analysis. Results The prevalence of past-year suicidal ideation was 14.0%. In the adjusted model, anxiety (AOR = 2.41, 95% CI: 1.12–5.17) and insomnia (AOR = 3.29, 95% CI: 1.24–8.73) were significantly associated, while students not engaged in thesis work (AOR = 0.37, 95% CI: 0.16–0.88) and not interested in publishing their theses (AOR = 3.450, 95% CI: 1.047–11.371) had higher odds of suicidal ideation. Among students engaged in thesis work, unadjusted analyses revealed significant associations between suicidal ideation and intention to publish thesis work, poor supervisor availability, unclear academic guidance, lack of publication support, and perceptions of a non-supportive institutional research environment. Conclusion Mental health challenges and academic exclusion—particularly non-thesis status and inadequate supervisory or institutional support—are key contributors to suicidal ideation. Universities should adopt inclusive research policies, enhance mental health services, and strengthen mentorship systems to reduce suicide risk and promote student well-being, especially in resource-constrained academic environments like Bangladesh.